PHYSICOCHEMICAL, ANTIOXIDANT, AND ANTIMICROBIAL PROPERTIES OF A SYNBIOTIC DRINK BASED ON MALABAR MELASTOME (MELASTOMA MALABATHRICUM L.) AND SOYMILK - SALAR, JOMARIE; Ramirez, Mary Ann Jilly (Food and Feed Research, 2026)
Malabar melastome (Melastoma malabathricum L.) is widely recognized for its pharmacological properties, particularly its rich antioxidant and antimicrobial content. This study examines the development and evaluation of a synbiotic drink formulated from Malabar melastome fruit juice and soy milk as a healthier alternative to conventional dairy-based probiotic beverages. A 3×3 full factorial experimental design generated nine treatment combinations, which were assessed for physicochemical characteristics (density, viscosity, pH, total soluble solids, and titratable acidity), bioactive compounds (total phenolic content, DPPH radical scavenging activity, total monomeric anthocyanin, saponin, and tannin), microbial viability, and antimicrobial activity. The drink incorporated a mixed culture of Lactobacillus acidophilus, Streptococcus thermophilus, and L. bulgaricus. Results indicated that the synbiotic drink exhibited desirable viscosity, balanced sweetness and acidity, and exceptional antioxidant activity, largely attributed to the bioactive compounds in Malabar melastome. Viable counts of L. acidophilus and L. bulgaricus ranged from 7.85 log CFU/mL to 8.13 log CFU/mL. In comparison, S. thermophilus ranged from 4.11 log CFU/mL to 4.38 log CFU/mL after 72 hours of incubation, confirming sufficient probiotic viability for synbiotic classification. Antimicrobial assay showed inhibitory effects only against Staphylococcus aureus (Gram-positive). Overall, the findings suggest that Malabar melastome enhances both the functional and microbial quality of LAB-enriched drinks, offering promise as a natural, functional ingredient in synbiotic beverage development.